2018
DOI: 10.1186/s12884-018-1925-8
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between maternal anxiety propensity and pregnancy outcomes?

Abstract: BackgroundSeveral studies have shown inconsistent associations between anxiety during pregnancy and adverse pregnancy outcome. This inconsistency may be due to lack of controlling for the timing and type of maternal anxiety. We aimed to isolate a specific type of anxiety - maternal anxiety propensity, which is not directly related to pregnancy, and evaluate its association with adverse pregnancy outcome.MethodsWe conducted a prospective observational study of 512 pregnant women, followed to delivery. The trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
14
0
3
Order By: Relevance
“…When restricted to studies investigating depression (Avalos, Chen, & Li, 2015; Bandoli & Chambers, 2017; Cripe, Frederick, Qiu, & Williams, 2011; Dayan et al, 2006; De Vera & Bérard, 2012; Goedhart et al, 2010; Henrichs et al, 2010; Hermon, Wainstock, Sheiner, Golan, & Walfisch, 2019; Heun-Johnson et al, 2019; Ibanez et al, 2012; Katon, Russo, Melville, Katon, & Gavin, 2012; Khanghah, Khalesi, & Rad, 2020; Kim et al, 2013; Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkala, 2000; Lutsiv et al, 2015; Mogos et al, 2019; Navaratne, Foo, & Kumar, 2016; Packer, Pilliod, Chatroux, Caughey, & Valent, 2019; Palmsten, Setoguchi, Margulis, Patrick, & Hernández-Díaz, 2012; Qiu, Sanchez, Lam, Garcia, & Williams, 2007; Ruiz et al, 2012; Schmidt et al, 2019; Suri et al, 2007; Venkatesh, Ferguson, Smith, Cantonwine, & McElrath, 2019; Yedid Sion, Harlev, Weintraub, Sergienko, & Sheiner, 2016; Yonkers, Gilstad-Hayden, Forray, & Lipkind, 2017), results indicated an increased risk of HDP (RR = 1.30; 95% CI 1.19–1.43; 26 studies). Analysis of studies on anxiety (Avraham, Tamar, Eyal, & Gali, 2020; Bánhidy, Ács, Puhó, & Czeizel, 2006; Catov, Abatemarco, Markovic, & Roberts, 2010; Chen, Lin, & Lee, 2010; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Ibanez et al, 2012; Kordi, Vahed, Rezaee, Reza, & Lotfalizadeh, 2017; Pavlov, Steiner, Kessous, Weintraub, & Sheiner, 2014; Ravid et al, 2018) also indicated an increased risk of HDP (RR = 1.49; 95% CI 1.13–21.98; 10 studies).…”
Section: Resultsmentioning
confidence: 99%
“…When restricted to studies investigating depression (Avalos, Chen, & Li, 2015; Bandoli & Chambers, 2017; Cripe, Frederick, Qiu, & Williams, 2011; Dayan et al, 2006; De Vera & Bérard, 2012; Goedhart et al, 2010; Henrichs et al, 2010; Hermon, Wainstock, Sheiner, Golan, & Walfisch, 2019; Heun-Johnson et al, 2019; Ibanez et al, 2012; Katon, Russo, Melville, Katon, & Gavin, 2012; Khanghah, Khalesi, & Rad, 2020; Kim et al, 2013; Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkala, 2000; Lutsiv et al, 2015; Mogos et al, 2019; Navaratne, Foo, & Kumar, 2016; Packer, Pilliod, Chatroux, Caughey, & Valent, 2019; Palmsten, Setoguchi, Margulis, Patrick, & Hernández-Díaz, 2012; Qiu, Sanchez, Lam, Garcia, & Williams, 2007; Ruiz et al, 2012; Schmidt et al, 2019; Suri et al, 2007; Venkatesh, Ferguson, Smith, Cantonwine, & McElrath, 2019; Yedid Sion, Harlev, Weintraub, Sergienko, & Sheiner, 2016; Yonkers, Gilstad-Hayden, Forray, & Lipkind, 2017), results indicated an increased risk of HDP (RR = 1.30; 95% CI 1.19–1.43; 26 studies). Analysis of studies on anxiety (Avraham, Tamar, Eyal, & Gali, 2020; Bánhidy, Ács, Puhó, & Czeizel, 2006; Catov, Abatemarco, Markovic, & Roberts, 2010; Chen, Lin, & Lee, 2010; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Ibanez et al, 2012; Kordi, Vahed, Rezaee, Reza, & Lotfalizadeh, 2017; Pavlov, Steiner, Kessous, Weintraub, & Sheiner, 2014; Ravid et al, 2018) also indicated an increased risk of HDP (RR = 1.49; 95% CI 1.13–21.98; 10 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Depression during pregnancy can also have adverse effects on the fetus, the most important of which are preterm labor and low birth weight [9]. Anxiety during pregnancy also increases the risk of preterm labor [10], low birth weight [11], preeclampsia and cesarean delivery [12].…”
Section: Introductionmentioning
confidence: 99%
“…39 In a study performed by Shapiro et al, 40 it was shown that premature birth was linked with the stress-related infections, but did not correlate with mental stress. In line with this, Ravid et al 41 demonstrated that anxiety was not associated with pregnancy complications. Contrarily, Ding et al 38 showed that maternal anxiety has a strong linkage with preterm delivery.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, preterm delivery is associated with the early increase in CRH. 41 Besides, elevated levels of CRH can increase the concentration of cortisol and estrogen. Heightened ratios of estrogen to progesterone may disturb the uterus tranquility, which could in-crease the risk of premature birth.…”
Section: Discussionmentioning
confidence: 99%